(untitled) (Intent Research Scientific Journal, 2023)
A question about the selection methods used in the creation of factory types of blue sheep selection, the history of the creation of sheep, the ways of their use in the establishment of factory types, the processes of application of the methods used in cattle farms. z has been conducted and the results of their implementation in production have been highlighted.